Supporting the global reduction of cervical cancer: challenges in colposcopy practice and training - Fujii, Takuma; Taira, Yusuke; Flannelly, Grainne; Nishizawa, Haruki; Tanaka, Yoshimichi (Frontiers in Oncology, 2025)
Colposcopy is an important element in the global challenge of reducing cervical cancer incidence. However, there are issues with expanding its use globally, including resources, training of colposcopists and quality assurance. This narrative review explores the role of colposcopists and the challenges of ensuring that practice and training are fit for purpose. The review found that colposcopy and colposcopists play three roles in managing cervical cancer: in diagnosis and interventions; communicating with patients; and supporting public education. It also found that colposcopy practices are evolving globally, alongside regional and national variations in vaccination, screening and treatment practices, creating important challenges. Many countries have introduced quality indicators or standards, but studies show significant variations from these in practice. Training of colposcopists also varies across regions. Some developed countries have defined curricula, but developing countries are more reliant on distance learning courses provided by international bodies. The review identified several ways to address these challenges, including setting standards for either practice or training, and training healthcare professionals from different backgrounds as colposcopists. New technologies such as artificial intelligence could also help. The review also identified some gaps in the literature, offering potential for further research. These include developing a consensus on the training needs in particular areas, and exploring how global or regional standards are applied at local levels, and how training for soft skills can best be delivered to colposcopists. It is considered essential that educational curricula should be tailored to the specific circumstances of each country or region.